Histamine Excretion by the Common Bed Bug (Hemiptera: Cimicidae). Issue 6 (10th September 2022) - Gaire, Sudip; Principato, Simona; Schal, Coby; DeVries, Zachary C
Abstract: The common bed bug ( Cimex lectularius L.) is a hematophagous pest species that lives in close proximity to humans. Following a blood meal, bed bugs deposit fecal material indoors. The feces contain a variety of compounds, including histamine, which serves as a component of their aggregation pheromone. Histamine is a pivotal mammalian immune modulator, and recently it was shown to be present in high concentrations in household dust from homes infested with bed bugs. To better understand the dynamics of histamine excretion, we analyzed bed bug fecal material from different life stages and populations, along with fecal material collected at different post-feeding times and from bed bugs fed on different diets. Our analysis showed significant variation in histamine excretion among life stages, with mated females excreting the most histamine and first instar nymphs excreting the least histamine. However, when histamine excretion was normalized for blood consumption, males were found to excrete more histamine than the other life stages. There was no difference in histamine excretion among laboratory and recently home-collected bed bug populations. Further, we found histamine excretion continued for at least 14 d post-feeding, with the highest amount of histamine excreted 3–4 d after a bloodmeal. Overall, this work demonstrates that bed bugs excrete histamine across all feeding life stages, populations, and at various times after feeding, and that histamine excretion is directly related to blood feeding. These results will be used to better understand the health risks associated with histamine excretion and potential mitigation strategies of environmental histamine.